Optical waveguides in benzocyclobutene (BCB 4024–40) polymer - Ibrahim, Mohd. Haniff (Penerbit UTM Press, 2010)
The fabrication and characterization processes of single mode optical waveguide based on photosensitive BenzoCyclobutene (BCB 4024–40) polymer are described. The polymer film thickness for various coating speed and refractive index are measured by the method of prism coupling. The waveguide is fabricated using the photolithography and chemical etching technique on BK7 glass substrate with a thin layer of SiO2 as cover. The waveguide loss is measured using the conventional cut back method which results on an average loss of 3.5 dB/cm.